Scoring magnetic resonance imaging (MRI) inflammation and structural lesions in sacroiliac joints of patients with axial spondyloarthritis: assessment of all MRI slices of the cartilaginous compartment versus standardized six or five slices. (3rd May 2020) - Krabbe, S; Kröber, G; Pedersen, SJ; Østergaard, M; Møller, JM; Sørensen, IJ; Jensen, B; Madsen, OR; Klarlund, M; Weber, U
Abstract : Objectives : The Spondyloarthritis Research Consortium of Canada (SPARCC) sacroiliac joint (SIJ) scoring system assesses six or five (6/5) semicoronal magnetic resonance imaging (MRI) slices for inflammation/structural lesions in patients with axial spondyloarthritis (axSpA). However, the cartilaginous SIJ compartment may be visible in a few additional slices. The objective was to investigate interreader reliability, sensitivity to change, and classification of MRI scans as positive or negative for various lesion types using an 'all slices' approach versus standard SPARCC scoring of 6/5 slices. Method : Fifty-three axSpA patients were treated with the tumour necrosis factor inhibitor golimumab and followed with serial MRI scans at weeks 0, 4, 16, and 52. The most anterior and posterior slices covering the cartilaginous compartment and the transitional slice were identified. Scores for inflammation, fat metaplasia, erosion, backfill, and ankylosis in the cartilaginous SIJ compartment were calculated for the 'all slices' approach and the 6/5 slices standard. Results : By the 'all slices' approach, three readers scored mean 7.2, 7.7, and 7.0 slices per MRI scan. Baseline and change scores for the various lesion types closely correlated between the two approaches (Pearson's rho ≥ 0.95). Inflammation score was median 13 (interquartile range 6–21, range 0–49) for 6/5 slices versus 14 (interquartile range 6–23, range 0–69) for all slices at baseline. Interreader reliability, sensitivity to change, and classification of MRI scans as positive or negative for various lesion types were similar. Conclusion : The standardized 6/5 slices approach showed no relevant differences from the 'all slices' approach and, therefore, is equally suited for monitoring purposes.